Functional and Quality of Life Outcomes of Multimodal Pain Management in Head and Neck Cancer Patients: A Case Series - Ocktarini, Rizky; Mahmud, Mahmud (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background: Head and neck cancer (HNC) is the sixth most common cancer globally. Patients often experience severe pain, impacting their functional status and quality of life (QoL). Multimodal pain management in head and neck cancer (HNC) is an evidence-based, integrated strategy that combines pharmacological interventions, interventional techniques, and non-drug therapies to target multiple pain pathways simultaneously, thereby optimizing relief while minimizing side effects and improving quality of life.Methods: This retrospective cohort study analyzed nasopharyngeal carcinoma (NPC) patients at Dr. Sardjito General Hospital (January-June 2023). Inclusion required histologically confirmed NPC with informed consent; exclusion criteria were life-limiting comorbidities or pre-terminal status. We assessed Karnofsky Performance Status (KPS), EORTC QLQ-C30, and Visual Analogue Scale (VAS) at baseline, 1-month, and 12-month intervals. Pain management strategies (pharmacological, physical therapy, psychosocial) were evaluated. Statistical analysis used paired t-tests with Bonferroni correction (SPSS v27; significance p<0.05). Ethical approval was obtained (KE-FK-1413-EC-2023).Results: Out of 23 initial candidates, 12 patients were included in the final analysis. Significant improvements were observed across all parameters: EORTC QLQ-C30 scores increased from a mean baseline of 69.6 to 88.6 at 1 month and 89.7 at 12 months (p < 0.01), KPS scores improved from 75 to 85 and 90 (p < 0.05), and VAS scores decreased from 8 to 5 and 3 (p < 0.05).Conclusion: A multimodal pain management approach significantly improves pain control and QoL in NPC patients. The combined use of NSAIDs, opioids, adjuvant medications, psychosocial support, and physical therapy demonstrates efficacy in managing pain and enhancing patient well-being.